2005
DOI: 10.1128/jcm.43.5.2350-2355.2005
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Aspects of the Investigation That Traced the 1998 Outbreak of Listeriosis in the United States to Contaminated Hot Dogs and Establishment of Molecular Subtyping-Based Surveillance for Listeria monocytogenes in the PulseNet Network

Abstract: A multistate outbreak of listeriosis occurred in the United States in 1998 with illness onset dates between August and December. The outbreak caused illness in 108 persons residing in 24 states and caused 14 deaths and four miscarriages or stillbirths. This outbreak was detected by public health officials in Tennessee and New York who observed significant increases over expected listeriosis cases in their states. Subsequently, the Centers for Disease Control and Prevention (CDC) began laboratory characterizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
70
0
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 27 publications
(19 reference statements)
6
70
0
6
Order By: Relevance
“…In our experience, overall, 11 clusters were identified among 54 human isolates from two different geographic areas of Italy based on serotyping and AscI pulsotypes and clustering confirmation by ApaI. In previous studies, AscI PFGE has provided evidence to accurately cluster epidemiologically related isolates and to separate isolates from different outbreaks, whereas the use of more-discriminatory ApaI PFGE as a primary approach led in some instances to inaccurate separation of epidemiologically related isolates (15). Consequently, a large proportion of the human listeriosis cases under investigation could be grouped into molecular subtype clusters, some of which could represent common-source outbreaks.…”
Section: Discussionmentioning
confidence: 78%
“…In our experience, overall, 11 clusters were identified among 54 human isolates from two different geographic areas of Italy based on serotyping and AscI pulsotypes and clustering confirmation by ApaI. In previous studies, AscI PFGE has provided evidence to accurately cluster epidemiologically related isolates and to separate isolates from different outbreaks, whereas the use of more-discriminatory ApaI PFGE as a primary approach led in some instances to inaccurate separation of epidemiologically related isolates (15). Consequently, a large proportion of the human listeriosis cases under investigation could be grouped into molecular subtype clusters, some of which could represent common-source outbreaks.…”
Section: Discussionmentioning
confidence: 78%
“…They found to be recorded an outbreak of 16 cases caused by pre-sliced ready-to-eat (RTE) delicatessen meat (sausage salad) [24]. Moreover, evidence from EU-wide routine food safety investigations indicates that a substantial proportion of RTE products may be contaminated by L. monocytogenes [25]. The result also confirms RTE, meat, and fish are as one of the important enteropathogens responsible for listeriosis.…”
Section: Discussionmentioning
confidence: 90%
“…PFGE has been considered as a standard subtyping method for L. monocytogenes [19]. The PFGE method has a high discriminatory power and has been shown to be very accurate and reproducible for fine structure comparison and molecular typing of L. monocytogenes [20] [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, their whole-genome macroarray strategy could not differentiate the 1998 outbreak isolates as a group from the 2002 outbreak isolates (9). Graves et al (6) and Kathariou (9) reported that ApaI PFGE could subgroup ECII isolates into four closely related clusters, with some clusters containing both the 1998 outbreak isolates and the 2002 outbreak isolates. In summary, isolates within each ECII outbreak had different genomic macroarray profiles and ApaI PFGE patterns; thus, the isolates within the same outbreak would be considered different strains according to the definition of strain given by the European Study Group on Epidemiological Markers (14).…”
mentioning
confidence: 99%
“…In summary, isolates within each ECII outbreak had different genomic macroarray profiles and ApaI PFGE patterns; thus, the isolates within the same outbreak would be considered different strains according to the definition of strain given by the European Study Group on Epidemiological Markers (14). Therefore, we propose "outbreak clone" as a better term than the traditional term "outbreak strain" to describe different strains involved in the same outbreak (6). Previously, AscI PFGE was the only subtyping method that could distinguish the 1998 outbreak isolates as a group from the 2002 outbreak isolates (Fig.…”
mentioning
confidence: 99%